Hidrolisis Daun Sawit Menjadi Glukosa Dengan Menggunakan Katalis H3PO4-H2SO4 - Fitriyanti Fitriyanti; Komalasari Komalasari; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Glucose is a simple monosaccharide containing an aldehyde group and six carbon atoms. Glucose is an intermediate product in biological and chemical conversion. Glucose can made from hydrolysis of biomass such as oil palm leaves. Previously, oil palm leaves are only used as fertilizer and animal feed. Biomass with the main component cellulose is very resistant to hydrolysis by water, therefor a catalyst in the form of acidic or alcalyc is needed. The purpose of this study was intended to examine the use of oil palm leaves as a raw material in the manufacture of glucose. There are two stages in this research, pretreatment and hydrolysis. The pretreatment using acid solvents with low concentrations of 0,5% H2SO4 with the cooking process at 80°C for 1 hour reaction time. The results showed that the acid pretreatment process using 0,5% H2SO4 solvent was able to increase cellulose 2%, hemicellulose 1%, and lignin reduction by 1%. The hydrolysis process is carried out in two stages, first stage is immersion of oil palm leaves with an H3PO4-H2SO4 catalyst ratio of 70:30 for 16 hours at room temperature. Then the second step is adding distilled water and cooked at a temperature variation of 100°C, 120°C and takes 2 hours, 3 hours and 4 hours. The highest glucose yield obtained from the hydrolysis process at 100°C for 4 hours at 26,8376% and the lowest glucose yield obtained from the hydrolysis process at 120°C for 4 hours at 18,1812%Keywords : Glucose, hydrolysis, oil palm leaves